Implementasi Random Forest Dengan LASSO Dalam Klasifikasi Penyakit Yang Ditularkan Melalui Nyamuk - Kadek Dwitya Adhi Pradyto; Made Agung Raharja (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Several diseases that can attack human health can be transmitted through disease vectors. One of the insects belonging to the disease vector is the mosquito. Diseases that can attack humans due to transmission through mosquitoes include malaria, dengue fever, chikungunya, yellow fever, rift valley fever, and many more. With so many types of diseases that are transmitted by mosquitoes and the symptoms that look quite similar, a classification process is carried out to distinguish the types of diseases. In this study, the classification was carried out using the Random Forest algorithm with the LASSO algorithm for feature selection. It was found that the average accuracy values of the Random Forest before and after carrying out feature selection using LASSO were 88% and 76%, respectively. From the values obtained, it can be concluded that the Random Forest has better performance without feature selection using the LASSO method.